(untitled) (Archives of Mechanics - Test, 2002)
A brief summary of professional career of Profesor Piotr Perzyna. Professor Piotr Perzyna was born on August 1, 1931 in the village of Niedżwiada near Łowicz in Poland. He recived the M.S. degree in 1956 from the Departmeat of Mechanical Engineering of Warsaw Technical University. He subsequently completed a Ph.D. in Mechanics of Solids at the Institute of Fundamental Technological Research, Polish Acacemay of Sciences in 1959 under the supervision of Professor Wacław Olszak. The academic year of 1961-1962 he spent abroad working as a Post Dac at Brown University with Professor William Prager. In 1963, he defended his D. Sc (habilitation) thesis.